2015
DOI: 10.1016/j.cognition.2014.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Even at 4 months, a labial is a good enough coronal, but not vice versa

Abstract: a b s t r a c tNumerous studies have revealed an asymmetry tied to the perception of coronal place of articulation: participants accept a labial mispronunciation of a coronal target, but not vice versa. Whether or not this asymmetry is based on language-general properties or arises from language-specific experience has been a matter of debate. The current study suggests a bias of the first type by documenting an early, cross-linguistic asymmetry related to coronal place of articulation. Japanese and Dutch 4-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
19
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 17 publications
5
19
1
Order By: Relevance
“…As outlined in the introduction, the language-independent biases documented here and in Tsuji et al (2015) align with asymmetries observed in word processing research with toddlers and neural processing research with adults. Clearly, these early perceptual biases are a precursor rather than a product of lexical development.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…As outlined in the introduction, the language-independent biases documented here and in Tsuji et al (2015) align with asymmetries observed in word processing research with toddlers and neural processing research with adults. Clearly, these early perceptual biases are a precursor rather than a product of lexical development.…”
Section: Discussionsupporting
confidence: 66%
“…Thus, this finding shows that perception of coronal-labial consonant place is asymmetric before attunement to native language phonetics or phonotactics is underway. Even so, early attunement would not explain the asymmetric findings reported by Tsuji et al (2015) because coronal consonants occur more frequently than labials in Dutch whereas the reverse pattern is found in Japanese.…”
Section: Introductioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Would infants fail to discriminate a prototypical exemplar from a subsequently presented less prototypical exemplar, but be able to discriminate the same two exemplars when they are presented in the reverse order? Note that there have been reports of asymmetry in discrimination between two consonants that are phonemically distinct in a child's language (e.g., Altvater-Mackensen & Fikkert, 2010;Tsuji et al, 2015;Nam & Polka, 2016). This kind of asymmetry within the native language is not what concerns us here; we aim to test possible asymmetry in non-native consonant perception, i.e., in perception of two segments which may have no straight-forward mapping onto distinct native language categories.…”
Section: Introductionmentioning
confidence: 96%